Hippasteria lepidonotus Fisher 1905 - Mah, Christopher L. (Zenodo, 2016)
Hippasteria lepidonotus (Fisher 1905) Ludwig 1905: 138 (as Hippasteria pacifica) Fisher 1905: 311;1911: 237; Lambert 1978a: 9; Maluf 1988: 34, 118; A.M. Clark 1993: 251; Mah et al. , 2010; Hendrickx et al. 2011:800 (as C. lepidonotus) Codoceo & Andrade 1978: 379 (as C. philippii) Pawson & Ahearn 2001: 42 (as Cryptopeltaster cf. lepidonotus) Comments. This was originally designated Cryptopeltaster Fisher 1905 before being reduced to the synonymy of Hippasteria by Mah et al. (2014). This species was observed feeding on gorgonians on Rodriquez and Davidson Seamount (Mah et al. , 2010). Occurrence. Chile, Galapagos, to Aleutian Islands (Alaska), including records from Rodriguez Seamount, Santa Cruz, California and British Columbia 188–1244 m. Published as part of Mah, Christopher L., 2016, Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species, pp. 101-141 in Zootaxa 4175 (2) on page 117, DOI:10.11646/zootaxa.4175.2.1, http://zenodo.org/record/257286